Urgensi Tabayyun pada Berita Hoaks Banjir Sumatera 2025 di Platform TikTok - Debi Ardila Sembiring; Muktarruddin Muktarruddin (Universitas Darussalam Gontor, 2026)
The development of social media, especially TikTok, has made it easier for people to obtain and disseminate information, including information about disasters. However, this convenience also increases the spread of unverified information, causing hoaxes. This study aims to analyze the urgency of tabayyun to information related to the 2025 Sumatra flood circulating on the TikTok platform and examine its relationship with digital literacy. The research uses a descriptive qualitative approach with a content analysis method. Data was obtained through observation and documentation of TikTok content that was purposively selected based on its suitability with the focus of the research. The results of the study show that content that does not have a clear source of information is still found as well as visual content that is indicated using Artificial Intelligence (AI) technology without explanation of its visual authenticity. These findings show the importance of verifying the source, content, and context of information before it is trusted or disseminated. In addition, this study shows that the principle of tabayyun is related to digital literacy because it both emphasizes the ability to examine information sources, verify, think critically, and consider the impact of information before making decisions. Therefore, tabayyun can be one of the guidelines in strengthening people's digital literacy to deal with the spread of disinformation on social media, especially in disaster situations.